THE HEALTH-CARE NEEDS AMONG OLDER PERSONS IN AN INDONESIAN URBAN SETTING - E, Setiawan; K, Poedjibudojo J; Ms, Tondok (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The unmet health-care needs among older persons population should be identified and anticipated due to hideous potential impacts. Ironically, no published study regarding this phenomenon was found in Indonesia. Derived from the Indonesian population and civil data, this study was conducted to identify the health-care needs of urban older people living on Java Island, the most populated island in Indonesia. Methods: A qualitative study was conducted in 3 subdistricts in Surabaya, the capital city of East Java, namely, Rungkut, Kenjeran, and Tenggilis. There were 9 focus group discussions (FGDs) conducted during March-August 2015. Participants in this study were recruited purposively, i.e., person in charge of Karang Werda,â€ and the discussion explored thematically various topics in the area of unmet health needs phenomena related to: (1) Availability, (2) accessibility, and (3) acceptability. A FGD guide was developed to ensure in-depth discussion. Results: There were 90 older persons serving as volunteers who participated in this study. The unmet health-care needs addressed by participants in this study were (1) Integrated and specialized health-care services for older persons and (2) skillful yet age-friendly health-care personnel were needed by participants. Our findings pointed out that the unmet health-care needs in Indonesian urban settings were classified as primarily availability, accessibility, and acceptability issues. Conclusion: The government needs to take actions to solve the challenges related to the fulfillment of health-care needs among older persons in Indonesia. Further study of the health care personnel’s beliefs and attitudes in providing care among older persons needs to be conducted to provide a more holistic picture of the phenomena before making any strategy for the future Indonesia’s health-care system.